In-field measurement and sampling technologies for monitoring quality in the sugarcane industry: a review - Mat Nawi, Nazmi; Chen, Guangnan; Jensen, Troy (Springer, 2014)
Reliable in-field quality measurement and sampling techniques are needed in the sugarcane industry to accommodate spatial variability in crop quality during harvesting. Existing in-field monitoring systems only monitor the crop yield and do not have the ability to measure product quality. This is a serious limitation for the industry in dealing with a significant quality variation across a field. Conventional technologies for measuring sugarcane quality in a laboratory have severe limitations for field use because they require complex sample preparation procedures especially to have clarified juice samples for each measurement. This review focuses on the use of current and new emerging precision agricultural sensing technologies for measuring product quality and describes their potential application and limitation for field use in the sugarcane industry. Optical spectroscopy is among the most promising technologies for measuring sugarcane quality on a harvester. The key considerations for development of a measurement method and sampling mechanism in the field are also discussed.